Recycled Paper as a Source of Renewable Jet Fuel in the United States - Kubic, William L.; Moore, Cameron M.; Semelsberger, Troy A.; Sutton, Andrew D. (Frontiers in Energy Research, 2021)
Converting biomass into jet fuel involves more than the core chemical process. The overall process includes the logistics of harvesting and transporting the biomass, handling and preparing the material for processing, and processing and disposal of waste. All of these activities contribute to cost. Controlling cost involves more than developing efficient process chemistry. Choice of feedstock also has a significant impact on process economics. We consider chemical conversion of paper from municipal solid waste as a feedstock for the production of jet fuel and diesel. Paper has a significantly higher cellulose content than raw lignocellulosic biomass such as corn stover, so it requires less pretreatment to convert it into hydrocarbons than lignocellulosic biomass. Our techno-economic analysis showed that the cost of converting paper waste into jet fuel is about 1.00/gal less than jet fuel produced from corn stover. Although the cost of recycling paper into jet fuel is less than producing it from corn stover, the process is not competitive with petroleum. We estimated a minimum selling price of 3.97/gal for paper-derived jet fuel. Our sensitivity studies indicated that the biggest economic obstacle is the cost of cellulose hydrolysis. Direct hydrogenation of paper to sugar alcohols combined with increased economy of scale could make recycling paper jet fuel competitive.